2-(4-Iodo-2, 5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25I-NBOME): A Harmful Hallucinogen Review. Issue 9 (3rd March 2020) - Kamińska, Katarzyna; Świt, Paweł; Malek, Kamilla
Abstract: NBOMes are N -benzylmethoxy derivatives of the 2C family compounds with N -2-methoxybenzyl moiety substituted by the methoxy group at the 2- and 5-position and the halogen group at the 4-position of the phenyl ring. These substances are a new class of potent serotonin 5-HT2A receptor agonist hallucinogens with potential harmful effects. The substitution with halogen of the already psychoactive phenethylamine produces a derivative (2C-I) with increased hallucinogenic effects. This class of hallucinogens has chemical structures very similar to natural hallucinogenic alkaloid mescaline and these are sold mainly via internet as a 'legal' alternative to other hallucinogenic drug-lysergic acid diethylamide (LSD). 25I-NBOMe is the first synthesized and one of the most common compound from NBOMes. Knowledge of pharmacological properties of 25I-NBOMe is very limited so far. There are only a few in vivo and in vitro so far published studies. The behavioral experiments are mainly related with the hallucinogenic effect of 25I-NBOMe while the in vitro studies concerning mainly the affinity for 5-HT2A receptors. The 25I-NBOMe Critical Review 2016 reported 51 non-fatal intoxications and 21 deaths associated with 25I-NBOMe across Europe. Case reports describe various toxic effects of 25I-NBOMe usage including tachycardia, hypertension, hallucinations, rhabdomyolysis, acute kidney injury and death. The growing number of fatal and non-fatal intoxication cases indicates that 25I-NBOMe should be considered as a serious danger to public health. This review aims to present the current state of knowledge on pharmacological effects and chemical properties of 25I-NBOMe and to describe reported clinical cases and analytical methods available for identification of this agent in biological material.